Factors influencing perceptions of learning environment among undergraduate medical students at a public university in Malaysia - Katiman, Ilmi Nadhrah (2020)
The medical education fraternity has widely acknowledged the importance of the learning environment in student learning. Previous studies have demonstrated the importance of the learning environment and its effect on the learning outcome, students’ motivation, educational program effectiveness, and academic achievements. This study aimed to assess learning environment perception (LEP) and factors influencing LEP among undergraduate medical students in Universiti Putra Malaysia (UPM). A crosssectional method and universal sampling were used in this study. Data collection was done from June to October 2018. From years one to five, medical students enrolled in the Bachelor of Medicine and Health Science (MBBS) program at the Universiti Putra Malaysia were recruited to participate in a questionnaire-based assessment. It contains to measure LEP, students’ demographic background, learning approach, quality of life, psychological distress level, resilience, and current affect. Students from the first and second years were grouped according to the respective classes, while students from the third, fourth, and fifth years were grouped according to the clinical teaching classes. They were briefed regarding the purpose of the study and reminded that participation is voluntary. On average, the respondents took 20 minutes to complete the questionnaire. Dundee Ready Educational Environment Measure (DREEM) was used, and descriptive statistics were applied. The inventory quantified the students’ overall LEP and divided the scores into five domains. The mean scores of each domain and the item building up the domain were calculated and ranked accordingly, and the overall score was summed up from all the items. By looking at the item ranks, the faculty were able to identify areas of strength and the problematic regions that need to be rectified. A Chi-square test was used to determine any association between LEP and other factors; learning approach, quality of life, psychological distress, resilience, and current affect. Significant associations were noted and applied in logistic regression to understand predictors that may influence higher LEP. A total of 440 out of 528 students responded in this study, yielding a response rate of 83.3%. Students rated their learning environment perception as positive, with a score of 136.06/200. Areas that are considered positive from the students’ perspective are the teachers who are knowledgeable and have a good rapport with patients, good friends, and motivated to participate in the course. This study also identified problematic areas, including overemphasising factual learning, teachers being authoritarian, cheating in the class, and abundant materials that need memorizing. The study also determined a significant relationship between deep and strategic approaches, presence of depression and anxiety, all aspects of quality of life (physical, psychological, social, and environmental), high affective and self- destructive trait when these factors were compared with LEP. Binary logistic regression analysis revealed factors that may result in higher learning environment perceptions, including having moderate to high social quality of life, adopting a strategic approach, not having depression, and having high affective traits. From these results, it may help the faculty in deciding which problem areas to focus on by accepting the negative feedbacks (factual learning, authoritarian teachers, cheating act, and abundant materials) from the students’ perspective, and recognizing efforts made by many (teachers, friends and inner motivating self). Furthermore, as predictors influencing learning environment had been identified, it may guide future directions of faculty to improve the LEP, and highlight to the faculty administration on the importance of students’ social quality of life, promoting students to adapt strategic approach, making sure the students are not depressed and understand students with a high-affective trait.